2019
DOI: 10.1001/jamaoncol.2018.4070
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hepatocellular Carcinoma in Patients Treated With Entecavir vs Tenofovir for Chronic Hepatitis B

Abstract: IMPORTANCE Entecavir and tenofovir disoproxil fumarate have comparable efficacy in achieving surrogate end points, including virologic response, and are equally recommended as first-line treatments for patients with chronic hepatitis B (CHB). However, it is unclear whether treatment with these drugs is associated with equivalent clinical outcomes, especially development of hepatocellular carcinoma (HCC).OBJECTIVE To compare entecavir and tenofovir in terms of the risk of HCC and death or liver transplant in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
367
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 249 publications
(387 citation statements)
references
References 33 publications
15
367
3
2
Order By: Relevance
“…14 Recently, a large nationwide Korean cohort study compared the incidence of HCC in CHB patients treated with entecavir vs TDF and found that the TDF group had a significantly lower risk of HCC (hazard ratio [HR] 0.61). 15 Caucasian CHB patients with cirrhosis who did not develop HCC also had similar 8-year survival compared to the general population. 16 However, almost all previous studies of TDF-treated patients did not have direct comparisons to CHB patients unexposed to anti-viral therapies or they had only small numbers of patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…14 Recently, a large nationwide Korean cohort study compared the incidence of HCC in CHB patients treated with entecavir vs TDF and found that the TDF group had a significantly lower risk of HCC (hazard ratio [HR] 0.61). 15 Caucasian CHB patients with cirrhosis who did not develop HCC also had similar 8-year survival compared to the general population. 16 However, almost all previous studies of TDF-treated patients did not have direct comparisons to CHB patients unexposed to anti-viral therapies or they had only small numbers of patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 81%
“…HCC rates in TDF‐treated patients were also lower after 5 years of treatment as compared to the first 5 years . Recently, a large nationwide Korean cohort study compared the incidence of HCC in CHB patients treated with entecavir vs TDF and found that the TDF group had a significantly lower risk of HCC (hazard ratio [HR] 0.61) . Caucasian CHB patients with cirrhosis who did not develop HCC also had similar 8‐year survival compared to the general population …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tenofovir and entecavir may differ in their effectiveness in the prevention of HCC for patients with chronic HBV infection. 4,5 Recently, tenofovir treatment was reported to be associated with a significantly lower risk of HCC compared with entecavir treatment for patients with chronic HBV infection. 4,5 Moreover, the authors evaluated the factors associated with development of HCC in the univariate and multivariate analysis as presented in Table 3.…”
Section: Letter: Clinical Outcomes After Long-term Entecavir or Tenofmentioning
confidence: 99%
“…4,5 Recently, tenofovir treatment was reported to be associated with a significantly lower risk of HCC compared with entecavir treatment for patients with chronic HBV infection. 4,5 Moreover, the authors evaluated the factors associated with development of HCC in the univariate and multivariate analysis as presented in Table 3. 1 However, family history of HCC, an important HCC risk factor, was not taken into consideration.…”
Section: Letter: Clinical Outcomes After Long-term Entecavir or Tenofmentioning
confidence: 99%